2019
DOI: 10.1038/s41433-019-0346-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of TGFBI corneal dystrophy and molecular diagnostic testing

Abstract: To date, 70 different TGFBI mutations that cause epithelial-stromal corneal dystrophies have been described. At present one commercially available test examines for the five most common of these mutations: R124H, R124C, R124L, R555W, and R555Q. To expand the capability of identifying the causative mutation in the remaining cases, 57 mutations would need to be added. The aim of this study was to obtain a better understanding of the worldwide distribution and population differences of TGFBI mutations and to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 24 publications
4
16
0
Order By: Relevance
“…The present study demonstrated that the mutations in the codons of R124 and R555, such as, R124H, R555W and R124C were the most common mutations in a multi-ethnic population in Singapore, corroborating well with the results of previous studies in different countries [ 2 , 5 , 8 , 19 , 20 , 21 , 22 , 23 , 24 ]. The predominance of R124H, R555W and R124C mutations in various geographical locations worldwide indicates that these mutations may represent mutation hot spots in the gene [ 2 ].…”
Section: Discussionsupporting
confidence: 92%
“…The present study demonstrated that the mutations in the codons of R124 and R555, such as, R124H, R555W and R124C were the most common mutations in a multi-ethnic population in Singapore, corroborating well with the results of previous studies in different countries [ 2 , 5 , 8 , 19 , 20 , 21 , 22 , 23 , 24 ]. The predominance of R124H, R555W and R124C mutations in various geographical locations worldwide indicates that these mutations may represent mutation hot spots in the gene [ 2 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our results provide a novel mechanistic insight into the function of DNA methylation in the pathogenesis of FECD and support further studies to determine how methylation of miR-199b-5p may be used as a clinical biomarker of phenotype expression in FECD. In the past few years, there have been major advances in testing blood, saliva, and cheek swab samples to genetically screen for corneal dystrophies 87,88 . Further studies are needed to determine if DNA methylation changes can be detected in these tissue samples that correspond to corneal methylation changes.…”
Section: Discussionmentioning
confidence: 99%
“…The TGFBI is a significant component of human corneal stroma involved in cell adhesion and migration, which is induced by its interaction with several ECM elements, including collagens ( Runager, Enghild & Klintworth, 2008 ). TGFBI variants have been frequently identified in patients with corneal dystrophies ( Chao-Shern et al, 2019 ), as well as KTCN ( Guan et al, 2012 ). While a significant upregulation of TGFBI in KTCN patients compared to control individuals was also detected previously ( Bykhovskaya et al, 2016a ), in most transcriptomic or proteomic studies the level of TGFBI in KTCN tissues was decreased ( Takács et al, 1999 ; Zhao et al, 2002 ).…”
Section: Discussionmentioning
confidence: 99%